ChemInform Abstract: Cobalt‐Catalyzed Enantioselective Hydroboration of 1, 1‐Disubstituted Aryl Alkenes. Issue 19 (May 2015) - Zhang, Lei; Zuo, Ziqing; Wan, Xiaolong; Huang, Zheng
Abstract Chiral cobalt methyl complexes having novel iminopyridineoxazoline ligands are developed and successfully applied to the asymmetric hydroboration of 1, 1‐disubstituted alkenes.